Elimination of Schistosomiasis Mekongi from Endemic Areas in Cambodia and the Lao People’s Democratic Republic: Current Status and Plans - Virak Khieu; Somphou Sayasone; Sinuon Muth; Masashi Kirinoki; Sakhone Laymanivong; Hiroshi Ohmae; Rekol Huy; Thipphavanh Chanthapaseuth; Aya Yajima; Rattanaxay Phetsouvanh; Robert Bergquist; Peter Odermatt (Tropical Medicine and Infectious Disease, 2019)
The areas endemic for schistosomiasis in the Lao People’s Democratic Republic and in Cambodia were first reported 50 and 60 years ago, respectively. However, the causative parasite Schistosoma mekongi was not recognized as a separate species until 1978. The infection is distributed along a limited part of the Mekong River, regulated by the focal distribution of the intermediate snail host Neotricula aperta. Although more sensitive diagnostics imply a higher figure, the current use of stool examinations suggests that only about 1500 people are presently infected. This well-characterized setting should offer an exemplary potential for the elimination of the disease from its endemic areas; yet, the local topography, reservoir animals, and a dearth of safe water sources make transmission control a challenge. Control activities based on mass drug administration resulted in strong advances, and prevalence was reduced to less than 5% according to stool microscopy. Even so, transmission continues unabated, and the true number of infected people could be as much as 10 times higher than reported. On-going control activities are discussed together with plans for the future.